Pendidikan Seks Dalam Gereja Sebagai Upaya Peningkatan Kualitas Moral Remaja - Siahaan, Ruth Judica (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
In this study the authors analyzed descriptively the independent variable Moral Quality of Youth and the Sex Education variable in the church. The sampling technique used in this study is saturated sample, which means the technique of determining the sample if all members of the population are used as samples. The results of this study also prove that the dominant indicator in forming the variable Moral Quality Improvement for Youth (Y) is a Significant Definition of Sex Education (X1) at Î± â‰¤ 0.05 by contributing 0.798 times. And the results of the study prove that the dominant aspect in shaping the variable enhancing adolescent moral quality (Y) is an indicator of educational background (X5) significantly at Î± â‰¤ 0.05.